Which name(s) should be used for Araucaria-like fossil wood?? Results of a poll - Röbler, Ronny (2014)
Araucarioxylon Kraus is a widely known fossil genus generally used for woods similar to that of the extant Araucariaceae. However, since 1905, several researchers have pointed out that this name is a junior nomenclatural synonym of various other taxa and, as such, a nomen illegitimum. At least four generic names are in current use for fossil wood of this type: Agathoxylon Hartig, Araucarioxylon, Dadoxylon Endlicher and Dammaroxylon Schultze-Motel. This problem of inconsistent nomenclatural application is compounded by the fact that woods of this type represent a wide range of plants including basal pteridosperms, cordaitaleans, glossopterids, primitive conifers, and araucarian conifers, with a fossil record that extends from the Devonian to Holocene. Conservation of Araucarioxylon has been repeatedly suggested but never officially proposed. Since general use is a strong argument for conservation, a poll was conducted amongst fossil wood anatomists in order to canvass current and preferred usage. It was found that the community is divided, with about one fifth recommending retention of the well-known Araucarioxylon, whereas the majority of others advocated use of the legitimate Agathoxylon. The arguments of the various colleagues who answered the poll are synthesized and discussed. There is clearly little support for conservation of Araucarioxylon. A secondary aspect of the poll tackled the issue as to whether Araucaria-like fossil woods should be either gathered into a unique fossil genus, or whether two fossil genera should be recognized, based on the respective presence or absence of axial parenchyma. A majority of colleagues favoured having one fossil genus only. Agathoxylon can be used legitimately and appears to be the most appropriate name for such woods. However, its original diagnosis must be expanded if those woods lacking axial parenchyma are to be included.